Control interno a los procesos de contratación pública y su incidencia en el manejo operativo de los requerimientos del Gad municipal del cantón Montalvo periodo 2016-2017 - Ulloa Fernández, Jennifer Kemberly (2018)
The internal control system allows guaranteeing the processes that are executed in the public procurement department, complying with the regulations and generating reliability, efficiency and effectiveness of the operations. The present investigation is focused on solving the problems that currently exist in the internal control of public procurement processes of the Municipal Autonomous Decentralized Government of Cantón Montalvo; whose objective is to evaluate the incidence of internal control based on the public procurement process in the operational management of the requirements of the GAD Municipal Canton Montalvo period 2016-2017, the methodology used was mixed qualitative-quantitative, the techniques were interviews and documentary review. The results show a deficient quality of the service granted through the requirements generated from the municipal dependencies, for these reasons it is desired to establish an adequate internal control over the processes in question. For this purpose, this surveillance is part of the internal control regulations and its total adherence to the business rules determined by the National Public Procurement Service; with this, it is sought to improve the performance and productivity in the different dependencies, directly or indirectly through the public servants of the requesting areas. To this end, it is proposed that the servers of the different agencies that are part of the contracting process be trained based on the applicable regulations, that the coordination of those involved in the preparation of the Annual Operating Plan be made effective, and then included in the web platform. of the National Public Procurement System. Keywords: Internal Control, Incidents, Payment Processes, Public Contracting